Surgical technique for explantation of a functioning cardiopulmonary complex in an experiment - M. O. Zhulkov; I. S. Zykov; A. G. Makaev; A. V. Protopopov; M. N. Murtazaliev; F. Yu. Kosimov; A. R. Tarkova; A. D. Limansky; Ya. M. Smirnov; H. A. Agaeva; O. E. Frykina; D. A. Sirota (Вестник трансплантологии и искусственных органов)
Objective: to develop and approve the surgical technique for explantation of a functioning cardiopulmonary complex under normothermic autoperfusion.Materials and methods. Landrace pigs were used as the experimental model for a series of acute experiments (n = 10). During the experiment, invasive pressure in the cavities of the heart and main arteries, blood gas composition, and myocardial contractility were monitored. The functioning cardiopulmonary complex was explanted through a median sternotomy. The explanted complex was conditioned at 37–38 °C for 6 hours.Results. In the course of a series of experiments, it was shown that stable operation of the isolated heart-lung complex ex vivo for 6 hours was fundamentally possible provided that the parameters of the basic homeostasis constants are maintained. The technological solutions used made it possible to ensure safe hemodynamic and anatomical isolation of the working cardiopulmonary complex.Conclusion. The developed protocol for isolating a functioning cardiopulmonary complex allows to provide stable graft function for 6 hours under normothermic autoperfusion. Implementation of this concept in the development of transport systems would significantly facilitate their design and eliminate the use of expensive components. This would contribute to widespread introduction into clinical practice.